Becoming Jane Austen : a life - Spence, Jon (Hambledon Continuum, 2007)
Chronicles the life of novelist Jane Austen, focusing on the factors which most influenced her life and work, including her relationship with Irish lawyer Tom Lefroy, which inspired her great love stories.